Dark Matter in the Universe - Adhikari, Devendra; Adhikari, Krishna Raj (BIBECHANA, 2010)
Different physical phenomena, techniques, and evidences which give the proof for the existence of dark matter have been discussed. Keywords: Baryonic matter; dark matter; Chandra x-ray Observatory DOI: 10.3126/bibechana.v6i0.3936 BIBECHANA Vol. 6, March 2010 pp.27-30